2015
DOI: 10.17582/journal.src/2015/2.3.36.53
|View full text |Cite
|
Sign up to set email alerts
|

The NonReligious-NonSpiritual Scale (NRNSS): Measuring Everyone from Atheists to Zionists

Abstract: Although hundreds of measures of personal religiousness and spirituality exist, none are capable of reliably and validly assessing individuals who identify as nonreligious and nonspiritual. There is a need to develop a valid and reliable measure of (non)religiousness and (non)spirituality. This article discusses these problems, and presents the development and initial validation of a 17-item Nonreligious-Nonspiritual Scale (NRNSS) across three studies. The NRNSS exhibited high internal consistency (α > .94) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
53
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 25 publications
0
53
0
3
Order By: Relevance
“…I have come across only one measurement scale that recognizes the distinction between the figurative and supernatural senses of spirituality. Cragun, Hammer, and Nielsen (2015) designed what they call the "NonReligious-NonSpiritual Scale" (NRNSS). They recognized that the two disparate senses of the word "spiritual" would compromise results with ambiguity, so they decided to specify one sense over the other, and stated it clearly in the instructions to eliminate any confusion: Some people use the terms "spirituality" and "spiritual" .…”
Section: Measuring Nonreligious/nonspiritual Identities With Surveysmentioning
confidence: 99%
“…I have come across only one measurement scale that recognizes the distinction between the figurative and supernatural senses of spirituality. Cragun, Hammer, and Nielsen (2015) designed what they call the "NonReligious-NonSpiritual Scale" (NRNSS). They recognized that the two disparate senses of the word "spiritual" would compromise results with ambiguity, so they decided to specify one sense over the other, and stated it clearly in the instructions to eliminate any confusion: Some people use the terms "spirituality" and "spiritual" .…”
Section: Measuring Nonreligious/nonspiritual Identities With Surveysmentioning
confidence: 99%
“…In fact, recent studies beginning to actually compare religious and nonreligious respondents support these articles (see, e.g., Cragun et al 2015;Cragun et al 2016). …”
mentioning
confidence: 93%
“…When studies demonstrated correlations between religious service attendance (the most common measure used in such studies, see Musick et al 2004 for review) and health outcomes, they missed the context that would suggest what these relationships actually meant (i.e., prevalence estimates) and without comparisons to nonreligious people that could have shown whether or not religion itself actually mattered (Cragun et al 2015). At the same time, religious service attendance could -as many studies have argued (Koenig 2012) and more recent studies contradict (Cragun et al 2016) -facilitate better health outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…I have come across only one measurement scale that recognizes the distinction between the figurative and supernatural senses of spirituality. Cragun, Hammer, and Nielsen (2015) designed what they call the "NonReligious-NonSpiritual Scale" (NRNSS). They recognized that the two disparate senses of the word "spiritual" would compromise results with ambiguity, so they decided to specify one sense over the other, and stated it clearly in the instructions to eliminate any confusion:…”
Section: Measuring Nonreligious/nonspiritual Identities With Surveysmentioning
confidence: 99%